Obesity and related risk of myeloproliferative neoplasms among israeli adolescents. Issue 7 (12th May 2017) - Leiba, Adi; Duek, Adrian; Afek, Arnon; Derazne, Estela; Leiba, Merav
Abstract : Objective: Obesity has been associated with various malignancies, but a clear association between overweight and myeloproliferative neoplasms (MPN) has not been established. Methods: This study assessed the association between adolescent obesity and future risk for MPN. Data on 2, 516, 256 Israeli adolescents, who underwent a compulsory general health examination at ages 16 to 19, between 1967 and 2011, were linked to the National Cancer Registry in this nationwide, population‐based cohort study. Cox proportional hazards models were used to estimate the hazard ratio (HR) for MPN associated with BMI measured at adolescence. Results: The mean follow‐up of 19.86 ± 12.15 years reflected 49, 977, 521 person years, during which 433 examinees developed MPN, primarily chronic myelogenous leukemia, polycythemia vera, and essential thrombocythemia. Obesity (BMI ≥ 95th percentile) in adolescence significantly predicted increased risk of MPN with HR (adjusted for sex) of 1.81 (95% confidence interval 1.13‐2.92, P = 0.014). Conclusions: Adolescent obesity might be related to an increased incidence of myeloproliferative neoplasms.